Sistemática de Licianthes (Dunal) Hassl. (Solanaceae) no Brasil - SILVA, Rafael Costa (2018)
With about 200 species, Lycianthes (Dunal) Hassler is one of the most representative genera of the Solanaceae family. The most complete treatment for the genus was done by Georg Bitter in 1919, who proposed an infrageneric classification system for Lycianthes, which included detailed descriptions of 134 species, however, it does not present illustrations or a key for identification of the treated species. For more than a century the species of Lycianthes were included in Solanum, due to the great morphological similarity of their flowers, evidenced mainly by the stellate corolla and the poricide anthers. On the other hand, the presence of appendages at the calyx evidences the great affinity of Lycianthes with Capsicum. Recent phylogenetic studies, including molecular studies have supported the position of Lycianthes in the Capsiceae tribe, reinforcing its phylogenetic affinity with Capsicum. In Brazil, the informations for Lycianthes are scarce, with the first records made in Flora Brasiliensis, where only two species were described as part of Solanum. Currently, the list of species of Flora do Brasil presents only one list with nine species of the genus. The present work was developed with the objective of carrying out a taxonomic study of Lycianthes for Brazil. For this, morphological, nomenclature and classic taxonomic studies were performed, complemented by anatomical studies. As a results, we present the taxonomic treatment of 12 species and a key to the separation of the Lycianthes species found in Brazil, including the description of a new species, a new combination, five synonymies, 14 lectopifications. In addition to the taxonomic treatment, a study of the leaf anatomy is presented, where the importance of these anatomical characters as a subsidy to the taxonomy of Lycianthes is evaluated. These results are organized in four manuscripts, of these, two manuscripts of taxonomy and nomenclature were already published in two specialized journals in 2018, and two other are being finalized to be submitted for publication in specialized journals: one presents a taxonomic review of Lycianthes species for Brazil, and the other brings the leaf anatomical data as support to the taxonomy of Lycianthes. This thesis represents an important contribution to the taxonomy of Lycianthes and fills a large gap of information about the taxonomy of the genus and constitutes the most complete treatment for the Lycianthes species of Brazil.